1987
DOI: 10.1002/1097-0142(19870701)60:1<31::aid-cncr2820600107>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Late cardiac effects of mediastinal radiotherapy in patients with Hodgkin's disease

Abstract: Twenty-eight patients younger than age 40 years, treated for Hodgkin's disease with mediastinal irradiation, were examined no less than 5 years after the irradiation in order to evaluate the frequency of cardiac abnormalities. Twelve patients (43%) had had some pericardial event after radiation: a diagnosed pericarditis, remarkably increased heart volume, or a conspicuous change of cardiac silhouette, suggesting pericardial fluid. On evaluation, 50% of the patients complained of symptoms, and 13 patients had t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0
1

Year Published

1990
1990
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(25 citation statements)
references
References 40 publications
2
20
0
1
Order By: Relevance
“…The linear accelerator of 25 MV used, gives a lower dose to the heart than 'Co or 8 MV LinAc as described in other studies (Brosius et al, 1981;Carmel & Kaplan, 1976;Cosset et al, 1984;La Monte et al, 1986;Larson et al, 1976;McReynolds et al, 1976;Pohjola-Sintonen et al, 1987;Watchie et al, 1987;Zarrabi et al, 1984); 1.8 Gy to a maximum of 2 Gy per fraction, five fractions per week, the two fields being treated every day, all these precautions are probably important to reduce late sequelae. Nevertheless, our follow-up is still too short to conclude.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…The linear accelerator of 25 MV used, gives a lower dose to the heart than 'Co or 8 MV LinAc as described in other studies (Brosius et al, 1981;Carmel & Kaplan, 1976;Cosset et al, 1984;La Monte et al, 1986;Larson et al, 1976;McReynolds et al, 1976;Pohjola-Sintonen et al, 1987;Watchie et al, 1987;Zarrabi et al, 1984); 1.8 Gy to a maximum of 2 Gy per fraction, five fractions per week, the two fields being treated every day, all these precautions are probably important to reduce late sequelae. Nevertheless, our follow-up is still too short to conclude.…”
Section: Discussionmentioning
confidence: 84%
“…Findings include acute but transient decreases in PFTs over the first 6 months with return to pretreatment values by 8-12 months (DoPico et al, 1979;Evans et al, 1974;Smith et al, 1989). Nevertheless Zuccali et al (1981), or Pohjola (1987 reported a significant decrease in vital capacity and inspiratory capacity in 30% of the patients, sometimes severe, more than 12 months after treatment. The follow-up of the patients in our series lasted more than 2 years and can explain our low sequelae level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations